2014
DOI: 10.3109/1061186x.2014.928714
|View full text |Cite
|
Sign up to set email alerts
|

Aceclofenac-loaded chondroitin sulfate conjugated SLNs for effective management of osteoarthritis

Abstract: CS-SLN could be potentially effective vector for the treatment or management of OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 25 publications
2
24
0
Order By: Relevance
“…The surface charge of SLN-LA was more negative as compared to SLN due to masking of positive charge of amine groups (SA) by LA during coupling. Drug entrapment was less in SLN-LA than SLN due to a bit leaching of the drugs during conjugation (32,33). Drug loading in SLNs for ALB and PRD was more than 70% because of hydrophobic nature of drugs.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The surface charge of SLN-LA was more negative as compared to SLN due to masking of positive charge of amine groups (SA) by LA during coupling. Drug entrapment was less in SLN-LA than SLN due to a bit leaching of the drugs during conjugation (32,33). Drug loading in SLNs for ALB and PRD was more than 70% because of hydrophobic nature of drugs.…”
Section: Discussionmentioning
confidence: 98%
“…on the luminal side of the BBB and degrading ecto-or endo-enzymes of the cytoplasm of endothelial cells prior to penetration into the brain (12). SLNs composed of biodegradable saturated lipids like HSPC are found to be biocompatible (13,14) and prolong blood circulation life because of enhanced in vivo stability (15,16). Pioneering characteristics of SLNs also extend many advantages such as controlled drug release (17), drug targeting and low biotoxicity, high drug payload, easy scale up, and amenability to sterilization (18,19).…”
Section: Introductionmentioning
confidence: 98%
“…Results revealed that the OP release was higher for both OPSLNs and OPSLNFs formulation in the initial hours, i.e. 34.76% and 32.56%, respectively reflecting a burst release of the drug [31]. Afterwards, formulations showed sustained release up to 144 h. After 144 h, drug release from OPSLNs and OPSLNFs was found to 99.39 ± 1.3% and 93.69 ± 1.1% that indicated sustained drug release pattern [32].…”
Section: Dsc Studiesmentioning
confidence: 93%
“…One molecule that has been used multiple times as a homing mechanism is chondroitin sulfate (CS) 61, 62 . This polysaccharide not only serves to target articular cartilage via certain binding motifs, but may also serve as a potential therapeutic agent.…”
Section: Articular Cartilage Targetingmentioning
confidence: 99%
“…In general, NSAIDs act as analgesics by inhibiting prostaglandin synthesis and cyclo-oxygenase enzyme (COX) activity, substances that cause pain and lead to other inflammatory processes 87 . To investigate whether NSAID-loaded NPs could reduce OA, solid lipid NPs with an NSAID (aceclofenac) with and without CS to target articular cartilage were injected intravenously (IV) into rats with chemically-induced OA using the MIA model 61 . The NPs with CS specifically targeted the inflamed knee joints inhibited edema to a greater degree than plain drug alone.…”
Section: Drugs That Inhibit Inflammationmentioning
confidence: 99%